The effect of COVID‐19 stay‐at‐home order and campus closure on the prevalence of acute respiratory infection symptoms in college campus cohorts. Issue 3 (4th March 2021) - Adenaiye, Oluwasanmi; Bueno de Mesquita, Paul Jacob; Wu, Qiong; Hong, Filbert; Lai, Jianyu; Chen, Shuo; Milton, Donald K.; ,
Abstract: Evaluation of population‐based COVID‐19 control measures informs strategies to quell the current pandemic and reduce the impact of those yet to come. Effective COVID‐19 control measures may simultaneously reduce the incidence of other acute respiratory infections (ARIs) due to shared transmission modalities. To assess the impact of stay‐at‐home orders and other physical distancing measures on the prevalence of ARI‐related symptoms, we compared symptoms reported by prospective college cohorts enrolled during two consecutive academic years. ARI‐related symptoms declined following campus closure and implementation of stay‐at‐home orders, demonstrating the impact of population‐based physical distancing measures on control of a broad range of respiratory infections.